Accessing visitor evaluation of an immersive cathedral experience: applying the Jungian lenses of feeling and thinking and Bailey’s theory of implicit religion - McKenna, Ursula (Journal of beliefs and values, 2025)
The SIFT hermeneutical approach, rooted in Jungian psychological type theory, distinguishes between two core cognitive processes: perceiving concerned with gathering information and judging concerned with evaluating information. The present study applies this approach to eliciting and interpreting visitor evaluation of an immersive cathedral installation (a pre-Christmas son et lumiere) by focusing on the evaluative lenses of feeling and thinking. Drawing on data from 545 visitors, analysis of qualitative responses to the feeling prompt, ‘What touched your heart during the installation or connected with your values?’ identified ten main themes. Analysis of qualitative responses to the thinking prompt, ‘What big questions were raised in your mind during the installation or connected with your interests?’ identified seven main themes. These two prompts generated quite different responses, suggesting a complementary and richer evaluation of the total experience could be accessed by engaging both the feeling function and the thinking function.